Absurdopedija russkoj žizni Vladimira Sorokina - Marusenkov, Maksim Petrovič (Aletejja, 2012)
Zsfassung in engl. Sprache
Literaturverz. S. 278 - 296
Keywords: Sorokin; Vladimir; Absurd (Philosophy) in literature; Grotesque in literature